Zarządzanie wiedzą personalną w organizacji - Jędrych, Elżbieta (Wydawnictwo Media Press, 2008)
Personal Knowledge Management (PKM) is necessary to any company which aims to survive and successfully compete on the market. It is the base of changes in personal function changes. Organizational HRM stays in challenge of changes both in surround environment and inside of today's organizations. It is strongly necessary to dispose of knowledge and skills on the field of collection, diffusion as well as storage of Personal Knowledge to fulfill those needs. Those skills are necessary for Personal Division and other units responsible for HRM in organization.
Keywords: zarządzanie wiedzą personalną; zarządzanie przedsiębiorstwem; transfer wiedzy; benchmarking kadrowy; business management; knowledge transfer; staffing benchmarking; personal knowledge management